2021
DOI: 10.1016/j.ejrad.2020.109398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of susceptibility-weighted imaging and susceptibility map-weighted imaging for the diagnosis of Parkinsonism with nigral hyperintensity

Abstract: To determine whether susceptibility map-weighted imaging (SMWI) was superior to conventional susceptibility-weighted imaging (SWI) in the diagnosis of Parkinson's disease (PD) and in its correlation with 123 I-2bcarbomethoxy-3b-(4-iodophenyl)-N-(3-fluoropropyl)-nortropane single photon emission computerized tomography ( 123 I-FP-CIT SPECT). Methods: Between May 2017 and February 2018, 125 consecutive patients diagnosed with idiopathic PD, vascular pseudoparkinsonism, essential tremor, or drug-induced parkinson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…A direct comparison of SMWI to standard SWI in the assessment of DNH resulted in a superiority of SMWI in terms of a higher interobserver agreement, a higher concordance rate with 123 I‐FP‐CIT SPECT and a higher diagnostic performance for PD 17 . Therefore, our results and the findings of previous studies using more advanced SWI techniques 16–19 emphasize the importance of appropriate technical standards to ensure a sufficient diagnostic accuracy of DNH in neurodegenerative parkinsonism. Particularly important in imaging the SN are a sufficient spatial resolution, the slice thickness and the signal‐to‐noise‐ratio (SNR) 20 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A direct comparison of SMWI to standard SWI in the assessment of DNH resulted in a superiority of SMWI in terms of a higher interobserver agreement, a higher concordance rate with 123 I‐FP‐CIT SPECT and a higher diagnostic performance for PD 17 . Therefore, our results and the findings of previous studies using more advanced SWI techniques 16–19 emphasize the importance of appropriate technical standards to ensure a sufficient diagnostic accuracy of DNH in neurodegenerative parkinsonism. Particularly important in imaging the SN are a sufficient spatial resolution, the slice thickness and the signal‐to‐noise‐ratio (SNR) 20 .…”
Section: Discussionsupporting
confidence: 59%
“…Notably, more advanced techniques like susceptibility‐map weighted imaging (SMWI), which can be generated from the SWI protocol by combining a magnitude image with a quantitative susceptibility mapping (QSM)‐based weighting factor, 15,16 were investigated to enhance the visibility of DNH by improving the contrast‐to‐noise ratio (CNR) 16 . A direct comparison of SMWI to standard SWI in the assessment of DNH resulted in a superiority of SMWI in terms of a higher interobserver agreement, a higher concordance rate with 123 I‐FP‐CIT SPECT and a higher diagnostic performance for PD 17 . Therefore, our results and the findings of previous studies using more advanced SWI techniques 16–19 emphasize the importance of appropriate technical standards to ensure a sufficient diagnostic accuracy of DNH in neurodegenerative parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…SWI sequences were considered to have a stronger and more accurate correlation with brain iron load than R 2 relaxation rate alone [38]. Studies have shown that this sequence is severely sensitive to mineralization and substances with magnetic susceptibility, hence, to be more sensitive than conventional gradient echo sequence in the detection of PD and parkinsonian syndromes [41,42].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%
“…Several studies have suggested that the loss of dorsolateral nigral hyperintensity on susceptibility-weighted imaging (SWI) (i.e., loss of the swallowtail appearance) indicates nigrostriatal dopaminergic degeneration and can thus be used as an imaging biomarker for IPD [ 3 4 5 6 7 ]. Furthermore, the visibility of the nigrosome 1 on MRI has been improved with “susceptibility map-weighted imaging (SMwI),” which resolves the blooming artifacts of SWI and improves the contrast-to-noise and signal-to-noise ratio [ 8 9 10 11 ] over SWI.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown the high diagnostic performances of both SWI and SMwI in determining the nigral hyperintensity in the substantia nigra [ 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 ]. However, these studies used heterogeneous study populations and imaging protocols, and discretionally chose different types of MR acquisition planes.…”
Section: Introductionmentioning
confidence: 99%